Policy Analysis: Solar Substitution with Biodiesel - Eddy Herjanto; IDK Kerta Widana (The Republic of Indonesia Defense University, 2016)
Industrial development and use of biodiesel in Indonesia is currently hampered by the cost of biodiesel for export opportunities. Manufacturers prefer to export biodiesel at a better price than selling in the country. The approach used in this research is qualitative. This study has produced a system dynamics models the behavior of the biodiesel industry in Indonesia. With this model, a formulated policies and strategies can be tested through simulation run that will show or predict system behavior biodiesel industry into the future. By formulating policies and strategies in various scenarios, each of which will give the results of system behavior biodiesel industry in the future, can be selected as optimal policy formulation strategy, in the sense of providing the most appropriate behavior with the desired behavior of the biodiesel industry.